Metody i narzędzia kształcenia zdalnego w polskich uczelniach w czasie pandemii COVID-19 – Część 1, Dyskusja 2020 - Topol, Paweł (Studia Edukacyjne, 2020)
The coronavirus has left its mark on practically every branch of the economy in Poland and has affected all spheres of human life: public, professional and private. Education is no exception. Distance learning, or e-learning, has a rich history in education. So far, however, e-learning has acted as a kind of “adjunct” to traditional classroom learning and as an alternative to face-to-face classes. The coronavirus disease forced a completely new situation in Polish education. All, or almost all, traditional forms of teaching and learning had to shift towards remote, virtual forms. In the first half of this year (2020), an extensive discussion at the SEA forum (the Academic E-learning Association) took place. Scientists, educators and technical experts from various academic centers spoke about the methods and tools launched in their institutions. This article offers a synthesis of that discussion, i.e. how certain Polish universities eventually did or did not succeed in the above matter. The article is based on selected fragments and quotes of the debate. Some of them were briefly commented on by the author.